The controllers' profile and their strategic choices: an analysis of Brazilian and Portuguese controller - Ferreira, M.; Edvalda, L.; Ferreira, A.; Ferreira, L. (Revista de Contabilidade e Organizações, 2021)
This article aims to understand how the values and cognitive basis proposed by the Upper Echelons Theory are seen in the strategic choices of controllers who work in companies in Brazil and Portugal. This is a descriptive study with a qualitative approach. Data were collected between the years 2018 and 2020 from interviews conducted with controllers and former controllers associated with companies from different sectors in these countries. A total of twenty-three interviews were conducted, and the data were analyzed using content analysis. The results revealed that previous professional experience and academic background, as well as the individual profile, the hierarchical structure, the organizational culture, and the level of autonomy given to the controllers interfere in their strategic choices in both countries. Collectivism, rationality, duty, and novelty were the values most emphasized by the interviewees as being essential to the position of controller.